Transformasi Digital dalam Edukasi Stunting untuk Meningkatkan Kesadaran Remaja Rumbuk Timur - Halimah, Robiatul Adawiyah; Mohammad Din Nur Ikhsani; Algi Hirlan Maulidi; Andre Faturrahman Al Khaffah; Yuyun Reka Asmayani; Muh. Ardika; Salas Wati; Bambang Maulidin; Irnia Yulisandra; M. Royyan Taslim; Febywan Saputri; Kariyalsi Adinda (Universitas Hamzanwadi, 2025)
The digital transformation in stunting education is an innovative initiative aimed at raising awareness among teenagers in Rumbuk Timur about the importance of stunting prevention. Stunting, a condition of impaired growth caused by chronic malnutrition, has significant impacts on the physical, cognitive, and social development of adolescents. This program leverages information technology to expand the reach of educational efforts, enhance social interaction in learning, and foster collective awareness among teenagers.By utilizing social media, mobile applications, and online learning platforms, the program provides easy access for teenagers to obtain information related to stunting anytime and anywhere. These technologies enable participants to engage in interactive discussions, watch educational videos, and share personal experiences through online platforms, enriching their understanding of the importance of balanced nutrition and stunting prevention. This Community Service Program (PKM) explores how digital technologies can be applied to enhance adolescent understanding, stimulate behavioral changes within families and communities, and create a sustainable positive impact. The results of the program indicate a significant increase in knowledge among teenagers, demonstrating the potential of technology as an effective tool in public health education